Peran Pemerintah Daerah dalam Meningkatkan Investasi Lokal - Hadijah Wahid, St.; Cinta, Cinta; Sabrina, Sabrina; Herlina, Herlina; Awalia, Reski; Asis, Asnita Binti; Al-Fajri, Aulia; Masyhudi, Din (PENG: Jurnal Ekonomi dan Manajemen, 2025)
Local governments play an important role in driving local economic growth through increased investment. Local investment can create jobs, increase community incomes and drive overall economic growth. Increasing local investment is key to driving regional economic growth. Local governments have an important role in creating a conducive environment for investors. The right strategies such as providing infrastructure, improving governance, promotion and facilitation, developing human resources, and supporting MSMEs can drive local investment and improve community welfare. Local governments have a very crucial role in utilizing the potential of Human Resources (HR) and Natural Resources (SDA) to encourage local economic growth. With several strategies implemented, one of which is by exploring and developing the potential of HR and SDA optimally, stimulating the growth and development of the regional economy through spatial planning that has a broad impact on the economy of the community in particular. The government is a group of people who have the power to create and implement laws and regulations in the region.